Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1111/j.1472-8206.2005.00376.x
|View full text |Cite
|
Sign up to set email alerts
|

Chemopreventive efficacy and anti‐lipid peroxidative potential of Jasminum grandiflorum Linn. on 7,12‐dimethylbenz(a)anthracene‐induced rat mammary carcinogenesis

Abstract: The aim of this study was to investigate the chemopreventive efficacy and anti-lipid peroxidative potential of Jasminum grandiflorum Linn. on 7,12-dimethylbenz(a)anthracene (DMBA)-induced rat mammary carcinogenesis. Mammary tumors were developed by a single subcutaneous injection of 25 mg DMBA in 1 mL emulsion of sunflower oil and physiological saline. The tumor incidence and tumor volume that formed in the breast were determined. Oral administration of ethanolic extract of J. grandiflorum flowers (JgEt) at a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…In this study, a significant decrease (p<0,05) was observed in the levels of vitamin C, between control and DMBA groups, which is consistent with Aralkumaran et al Ascorbic acid protects against the genotoxic effects of several radical-generating mutagens, enzymatic superoxidegenerating system (hypoxanthine/xanthine oxidase) DMBA [48]. In another study, researchers demonstrated that Vitamin C, an important extracellular antioxidant, has benefical effects on the conversion of cancerous cells to normal ones and in the lipid peroxidation by product scavenging mechanism [49].…”
Section: Level Of Vitaminssupporting
confidence: 72%
“…In this study, a significant decrease (p<0,05) was observed in the levels of vitamin C, between control and DMBA groups, which is consistent with Aralkumaran et al Ascorbic acid protects against the genotoxic effects of several radical-generating mutagens, enzymatic superoxidegenerating system (hypoxanthine/xanthine oxidase) DMBA [48]. In another study, researchers demonstrated that Vitamin C, an important extracellular antioxidant, has benefical effects on the conversion of cancerous cells to normal ones and in the lipid peroxidation by product scavenging mechanism [49].…”
Section: Level Of Vitaminssupporting
confidence: 72%
“…This herb is also used as an alternative treatment for cancers and for viral and bacterial infections. Research by Kolanjiappan and Manoharan (2005) demonstrated a strong chemoprevention against experimental mammary carcinogenesis in rats.…”
Section: Introductionmentioning
confidence: 99%
“…Mammary carcinogenesis was induced in Sprague-Dawley rats using a single subcutaneous injection of 25 mg of DMBA in 1 ml emulsion of sunflower oil (0.75 ml) and physiological saline (0.25 ml) to each rat (Kolanjiappan and Manoharan, 2005).…”
Section: Induction Of Mammary Carcinogenesismentioning
confidence: 99%